' ¡Uy!, ¿quién pidió pollo?' A qualitative analysis of the piropo practice by construction workers in Bogotá, Colombia. (26th July 2016) - Ramírez-Cruz, Héctor; Correa, Nataly; Mancera, Jennifer
Abstract : This paper analyzes the discursive practice of piropos performed by construction workers and addressed to female pedestrians in Bogotá, Colombia. Following an interactional sociolinguistic approach, the paper investigates the distinctive features of the piropo practice within this group. The investigators collected 87 naturalistic interactions and 40 interviews of speakers using ethnographic techniques. The analysis includes the study of the content and the form of piropos along with body language and the general performance of the speaker and the addressee. The results show that the speakers follow the patterns of piropo interactions in the Hispanic culture, even though they use speciﬁc features for the preparatory acts, the enunciation, and the offset of piropos. The observational data suggest that the practice is grounded on machismo ideologies that trigger public deployment of masculinity. On the other hand, interview data display speakers' perceptions of piropos as a ﬂirtatious activity and a verbal game. The paper provides naturalistic evidence of the piropo practice in a Hispanic context and contributes to the discussion of gender roles in the public space.